Patterned Colouring via Variable-Speed Single Stretching - Xuelian Wu; Vishwa Mohan Tiwari; Kimaya Prasad Suryarao; Richard Tan; Rui Xiao; Haibao Lv; Yilei Zhang; Zhifeng Wang; Wei Min Huang (Inventions, 2022)
We demonstrate a cost-effective, highly reliable/stable and environmentally friendly approach for the patterned colouring of a commercial transparent polyethylene terephthalate (PET). We show that different colour patterns (transparent, white/translucent, complete white/silver and different combinations of these three colours) can be realised in PET strips upon varying the speed during continuous stretching. The conditions for good quality colour patterns are investigated, and the length of transient region during speed change is investigated.